Knowledge of the inhabitants of Upper Silesia patients’ rights - Kryska, Sandra; Rej, Anna; Horák, Stanisław (Polish Journal of Public Health, 2013)
Introduction. Patients’ rights are the rights available equally to everyone for the use of health services. Therefore, every patient should know their rights and know how to use them. In Polish law, the most important document relating to issues of patient rights is the Act of 6 November 2008 on the Patient’s Rights and the Patients Ombudsman. This Act includes provisions relating to the rights of such patients as well as records relating to ways to assert their rights in the event of a medical event. Aim. The aim of this study was to investigate the level of awareness and knowledge of patients’ rights among persons enjoying the benefits of selected health care facilities in Upper Silesia. Material and methods. The study was conducted from September 2011 to January 2012 in a group of 1000 patients in selected health care facilities in Silesia. The study authors used a questionnaire completed anonymously by each patient. Results. Based on the analysis of the questionnaires, it was found that patients know about the existence of laws that protect them. The vast majority of them, however, cannot specify their rights and they cannot specifically indicate their use. Conclusions. The level of awareness of patients’ rights in the study population did not differ significantly from the level of awareness of the respondents participating in other studies. Awareness and knowledge of these rights of patients is incomplete, insufficient and depends, among others by: gender, age and education. The presented data suggests that patients should still know the rights to which they are entitled